2014
DOI: 10.1158/1078-0432.ccr-13-3003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Patient-Matched Brain and Extracranial Melanoma Metastases Implicates the PI3K Pathway as a Therapeutic Target

Abstract: Purpose An improved understanding of the molecular pathogenesis of brain metastases, one of the most common and devastating complications of advanced melanoma, may identify and prioritize rational therapeutic approaches for this disease. In particular, the identification of molecular differences between brain and extracranial metastases would support the need for the development of organ-specific therapeutic approaches. Experimental Design Hotspot mutations, copy number variations (CNV), global mRNA expressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
152
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(166 citation statements)
references
References 42 publications
14
152
0
Order By: Relevance
“…Multidimensional molecular profiling of matched cerebral and extracerebral melanoma metastases found no differences in hotspot mutations, copynumber variations, mRNA and protein expression, but detected increased expression of several activation-specific protein markers of the PI3K-AKT pathway in brain metastases (16). Furthermore, in a retrospective analysis, complete loss of the phosphatase PTEN, which inhibits PI3K, correlated with more rapid brain metastasis formation and decreased overall survival in stage IIIB/C melanoma patients with BRAFV600 mutations (20).…”
Section: The Pi3k Inhibitor Buparlisib Inhibits Growth Of Braf-and Nrmentioning
confidence: 89%
“…Multidimensional molecular profiling of matched cerebral and extracerebral melanoma metastases found no differences in hotspot mutations, copynumber variations, mRNA and protein expression, but detected increased expression of several activation-specific protein markers of the PI3K-AKT pathway in brain metastases (16). Furthermore, in a retrospective analysis, complete loss of the phosphatase PTEN, which inhibits PI3K, correlated with more rapid brain metastasis formation and decreased overall survival in stage IIIB/C melanoma patients with BRAFV600 mutations (20).…”
Section: The Pi3k Inhibitor Buparlisib Inhibits Growth Of Braf-and Nrmentioning
confidence: 89%
“…Of note, inhibition of the PI3K-AKT pathway with the PI3K inhibitor GDC-0941 leads to growth inhibition of brain metastasis-derived melanoma cells in vitro. Upregulation of the PI3K-AKT pathway was also reported in a recent study of matched cerebral and extracerebral metastasis samples using analysis of hotspot mutations, copy-number variations, mRNA expression patterns, quantitative analysis of protein expression, and activation by reverse-phase protein array analysis (2).…”
Section: ó2015 Aacrsupporting
confidence: 59%
“…1). A preferential upregulation of the PI3K-AKT pathway was recently recognized in cerebral compared with extracerebral metastases (2), and loss of PTEN was correlated with earlier development of brain metastases (3), perhaps as a result of an intrinsic activation of tropism for the cerebral microenvironment. The PI3K-AKT pathway in melanoma is commonly activated via mutations in NRAS or loss of PTEN (4).…”
Section: ó2015 Aacrmentioning
confidence: 99%
“…Molecular profiling of matched CNS and extracranial metastases in smaller series of melanoma patients showed that CNS metastases distinguished themselves through specific molecular differences in the activation of the PI3K/mTOR/ Akt or HER2 or kirsten rat sarcoma (KRAS) pathway. [28][29][30][31] These studies highlight, for example, the potential of adding PI3K inhibitors or mTOR inhibitors as adjunct targeted therapy in the treatment of CNS metastases.…”
Section: Molecular Mechanisms Of Central Nervous System Metastasis Fomentioning
confidence: 99%